2011
DOI: 10.3389/fpsyg.2011.00042
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Measurement of Face Recognition in Rapid Serial Visual Presentation

Abstract: Event-related potentials (ERPs) have been used extensively to study the processes involved in recognition memory. In particular, the early familiarity component of recognition has been linked to the FN400 (mid-frontal negative deflection between 300 and 500 ms), whereas the recollection component has been linked to a later positive deflection over the parietal cortex (500–800 ms). In this study, we measured the ERPs elicited by faces with varying degrees of familiarity. Participants viewed a continuous sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 27 publications
2
40
0
Order By: Relevance
“…In addition, in visual recognition tasks, components of the evoked potentials at around 500-600 ms are also known to be responsible for recollection (for review Friedman and Johnson, 2000), their amplitude being related to the amount of knowledge of the observed stimulus (Smith, 1993;Touryan et al, 2011). It is therefore possible that the information coded by the primary motor cortex participates in the recollection process, probably because the knowledge related to the movement is necessary to produce the letter is critical.…”
Section: Motor Familiarity Effects On Erpsmentioning
confidence: 96%
“…In addition, in visual recognition tasks, components of the evoked potentials at around 500-600 ms are also known to be responsible for recollection (for review Friedman and Johnson, 2000), their amplitude being related to the amount of knowledge of the observed stimulus (Smith, 1993;Touryan et al, 2011). It is therefore possible that the information coded by the primary motor cortex participates in the recollection process, probably because the knowledge related to the movement is necessary to produce the letter is critical.…”
Section: Motor Familiarity Effects On Erpsmentioning
confidence: 96%
“…In 2013, Kaufmann et al compared familiar personally-known faces to familiar famous faces based on the findings of Touryan, Gibson, Horne, and Weber (2011), who found that familiar family faces to elicit larger N400 responses than familiar famous faces. In the nondisabled sample, it was found that performance was significantly different between the classic character flash condition (CF) and the face conditions (FF) but there was no significant difference between the two FF conditions.…”
Section: Faces As Stimulimentioning
confidence: 99%
“…In this paradigm, each image replaces the previous one at the same spatial location. Single-trial detection of ERPs has been addressed in several problems such as target detection by using RSVP tasks, e.g., the search of targets in satellite images (Bigdely-Shamlo et al, 2008;Gerson et al, 2006;Parra et al, 2008), face recognition (Touryan et al, 2011). Target detection has also been the subject of a recent competition in an international machine learning workshop (MLSP) (Hild et al, 2010).…”
Section: Introductionmentioning
confidence: 99%